Standardized Xylocarpus moluccensis fruit fraction mitigates collagen‐induced arthritis in mice by regulating immune response. (9th February 2020) - Gupta, Priya; Kumar, Amit; Pal, Subhashis; Kumar, Sachin; Lahiri, Amit; Kumaravelu, Jagavelu; Chattopadhyay, Naibedya; Dikshit, Madhu; Barthwal, Manoj Kumar
Abstract: Objective: This study was undertaken to evaluate the effect of Xylocarpus moluccensis fruit fraction (F018) on the pathogenesis of collagen‐induced arthritis in mice. Methods: Arthritis was induced by intradermal injection of collagen (2 mg/ml) with complete Freund's adjuvant in DBA/1J mice. F018 was administered orally at 1, 3 and 10 mg/kg for 20 days. Disease progression and mechanism were assessed by micro‐CT analysis, RT‐PCR, flow cytometry assay, myeloperoxidase (MPO) and MTT assay. Results: F018 at 3 and 10 mg/kg significantly reduced paw thickness, clinical score, mononuclear cell infiltration and collagen layer depletion in the knee section of collagen‐induced arthritis (CIA) mice when compared with collagen‐induced arthritis mice alone. Furthermore, F018 treatment in collagen‐induced arthritis mice significantly recovered bone volume and trabecular number and decreased the trabecular space by modulating RANKL and OPG mRNA expression in the synovial tissue. F018 treatment in collagen‐induced arthritis mice significantly attenuated spleen index, lymphocyte proliferation and paw myeloperoxidase (MPO) activity, pro‐inflammatory cytokine TNFα, IL1β, and IL6 mRNA expression and enhanced IL10 mRNA expression in paw tissue. Furthermore, F018 treatment in collagen‐induced arthritis mice significantly reduced splenic dendritic cell maturation and Th17 cells. In culture, F018 significantly decreased collagen‐induced arthritis‐FLS proliferation and promoted apoptosis. Conclusion: F018 may serve as a potential curative agent for arthritis.